PENGARUH PENGETAHUAN DAN KEMUDAHAN TERHADAP KEPUTUSAN PENGGUNA DAN KEPUASAN KONSUMEN DALAM MELAKUKAN TRANSAKSI NON TUNAI QRIS (QUICK RESPONSE CODE INDONESIAN STANDARD) DI KOTA PEKANBARU - Isra, Ade Indriana; Wasnury, Rendra; Noviasari, Henny (Jurnal Ekonomi Bisnis Kompetif, 2024)
This study aims to determine how much influence the things that influence User Decisions and Consumer Satisfaction in Making Non-Cash Transactions QRIS (Quick Response Code Indonesian Standard) in Pekanbaru City. Primary data was collected using a questionnaire as an instrument and structured interviews were used as a complement in proving the research results. This study used 100 samples of QRIS (Quick Response Code Indonesian Standard) users in Pekanbaru City as respondents using the Non Probability Sampling Technique. With the minimum age of 17 years, using, having made non-cash transactions using QRIS, and domiciled in Pekanbaru City. The method used is Explanatory Research with data analysis tests, instrument tests, classic assumption tests, hypothesis testing, and path analysis as data testing paths as well as by the statistical product and service solution software application (SPSS version 21). The results of this study indicate that (1) Knowledge influences User Decisions in Making Non-Cash Transactions QRIS (Quick Response Code Indonesian Standard) in Pekanbaru City; (2) Convenience has an effect but is weak on User Decisions in Making Non-Cash Transactions QRIS (Quick Response Code Indonesian Standard) in Pekanbaru City; (3) User Decisions affect Consumer Satisfaction in Using QRIS (Quick Response Code Indonesian Standard) Non-Cash Transactions in Pekanbaru City; (4) The direct effect of knowledge on user decisions is greater than the indirect effect of knowledge on user decisions and consumer satisfaction in conducting QRIS non-cash transactions in Pekanbaru City (5) the direct effect of convenience on decisions is greater than the indirect effect of convenience on customer satisfaction in Conduct QRIS Non-Cash Transactions in Pekanbaru City. Keywords: Non-Cash Transactions, Convenience, Knowledge, User Decision, Consumer Satisfaction